2014
DOI: 10.1111/afe.12090
|View full text |Cite
|
Sign up to set email alerts
|

Goldspotted oak borer effects on tree health and colonization patterns at six newly-established sites

Abstract: 1 Newly-established populations of invasive wood-inhabiting insects provide an opportunity for the study of invasion dynamics and for collecting information to improve management options for these cryptic species. 2 From 2011 to 2013, we studied the dynamics of the goldspotted oak borer Agrilus auroguttatus Schaeffer (Coleoptera: Buprestidae), a new pest of oaks in southern California, at six sites that had been colonized recently. 3 At all sites, the percentage of coast live oaks Quercus agrifolia Née, coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Certainly, the degree of success A. biguttatus can have in the final stages of decline can be dramatic, as highlighted by the emergence of 102 beetles in an eight-week period from a heavily declined tree (that died in the following year). A similar pattern can be seen with Agrilus auroguttatus Schaeffer, where a small number of symptomatic trees produce the majority of emerging adults [58].…”
Section: Discussionsupporting
confidence: 59%
“…Certainly, the degree of success A. biguttatus can have in the final stages of decline can be dramatic, as highlighted by the emergence of 102 beetles in an eight-week period from a heavily declined tree (that died in the following year). A similar pattern can be seen with Agrilus auroguttatus Schaeffer, where a small number of symptomatic trees produce the majority of emerging adults [58].…”
Section: Discussionsupporting
confidence: 59%
“…Because many insects prefer to colonize weakened or previously infested trees rather than healthy trees, we examined the effect of previous infestation levels on subsequent infestation by A. auroguttatus and on the rate of decline of the oaks. We also measured infestation levels as they related to trunk diameter to confirm observations by our group that had suggested that larger diameter trees were more likely to be colonized by A. auroguttatus . We selected two study sites in the core area of the zone of infestation in San Diego County, California (Fig.…”
Section: Introductionmentioning
confidence: 61%
“…C). At newly infested sites on the periphery of the zone of infestation, Q. agrifolia in the 11–20 cm diameter class were rarely infested, whereas greater proportions of Q. agrifolia in the larger diameter classes were infested and, in particular, brood trees were observed in the larger diameter classes (>41 cm DBH) . At both Deerhorn Valley and Japatul Valley, the greatest cumulative increase in emergence holes was observed on trees with an intermediate DBH (between 20 and 41 cm) (Figs A and B).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At each site, 10 trees infested with larval A. auroguttatus were selected for deployment of A. auroguttatus sentinel eggs to survey for potential natural enemies targeting this life stage in the native and invaded ranges. Previously infested trees were selected because they appear to be more attractive to A. auroguttatus adults Haavik, Flint, Coleman, Venette, & Seybold, 2014). Trees were considered infested if symptoms described in Hishinuma et al (2011) such as larval galleries and exit holes were present.…”
Section: Study Sitesmentioning
confidence: 99%